Eradication of hepatitis C virus preserve liver function and prolong survival in advanced hepatocellular carcinoma patients with limited life expectancy. Issue 2 (6th October 2020) - Yeh, Ming‐Lun; Kuo, Hsing‐Tao; Huang, Ching‐I; Huang, Chung‐Feng; Hsieh, Ming‐Yen; Liang, Po‐Cheng; Lin, I‐Hung; Hsieh, Meng‐Hsuan; Lin, Zu‐Yau; Chen, Shinn‐Chern; Dai, Chia‐Yen; Huang, Jee‐Fu; et al.
Abstract: Whether patients with advanced hepatocellular carcinoma (aHCC) benefit from hepatitis C virus (HCV) eradication is uncertain. We aimed to investigate whether a survival benefit was conferred by HCV eradication in aHCC patients. This retrospective cohort study enrolled 168 HCV‐infected aHCC patients from April 2013 to January 2019. All patients were treated with sorafenib. Endpoints included overall survival (OS), progression free survival (PFS), and time to liver decompensation. Patients with undetectable HCV RNA exhibited reduced aspartate aminotransferase and alpha fetoprotein levels, as well as an attenuated proportion of aHCC at initial diagnosis but increased albumin and mean sorafenib daily dosing. Patients with undetectable HCV RNA exhibited significantly longer OS compared to patients with detectable or unknown HCV RNA, which was an independent factor of OS (HR: 0.56, 95% CI: 0.350‐0.903, P = .017). Patients with undetectable HCV RNA also presented a trend for longer PFS (HR 0.68, 95% CI: 0.46‐1.00, P = .053). The survival benefit was considered with respect to the significantly prolonged time to Child‐Pugh B scores in patients with undetectable HCV RNA (HR 0.59, 95% CI: 0.38‐0.92, P = .020). Patients with detectable HCV RNA at sorafenib initiation who further received direct acting antiviral therapy also had significantly longer OS (HR 0.11, 95% CI: 0.02‐0.81, P = .030) and PFS (HR 0.23, 95% CI: 0.06‐0.99, P = .048). In conclusion, abolishing HCV viremia preserves liver function and confers a survival benefit in advanced HCC patients on sorafenib treatment.